ASSESSING THE IMPORTANCE OF SUPPLY CHAIN MANAGEMENT IN STRENGTHENING THE MSMES RESILIENCE IN THE TIME OF DISRUPTION - Arkananta, Muhammad Bagas; Mcguinness, Gary (JURNAL AKUNTANSI DAN AUDITING, 2024)
In the current dynamic business landscape, organizations need to be able to quickly adjust to changing conditions and protect its business against various risks in order to stay competitive. Due to its severe disruption of global supply chains, particularly in the food sector, the COVID-19 pandemic has brought attention to the need for strong supply chain management (SCM) strategies. This study investigates how resilient MSMEs supply chains are, in case of Dfresto company as an MSME in the Indonesian food industry that benefited from the Covid-19 pandemic. In order to reduce the disruptions impact on the MSMEs level, the study identifies some important things that contribute to the supply chain resilience, such as the importance of having various suppliers and an organized distribution network. Moreover, the research proposes strategies for MSMEs to improve the resilience of their supply chains, like maintaining positive relationships with suppliers and having a short payment term to ensure a steady cash flow. The results could provide MSMEs with important information to build more sustain supply chain networks and better prepare for unanticipated circumstances in the future.